2018
DOI: 10.1177/0738894218787783
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Colombian attitudes toward the peace process

Abstract: A critical element that is often overlooked when studying negotiations in civil wars is popular support for the peace process itself. This is particularly important when agreements are subject to ratification by the broader population, as was the case in the Colombian conflict with the FARC. Using survey data from 2014, we find that attitudes toward this peace process were driven by political preferences more than conflict experiences. Some demographic traits (education, religion, and rural residency) were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…21 The analysis also shows that other factors had an impact on support for the peace agreement. First, and in line with previous findings (Fergusson and Molina 2016;Liendo and Braithwaite 2018;Weintraub et al 2015), municipalities with higher levels of support for Santos in the 2014 presidential elections were more prone to vote yes in the referendum (p < 0.01). This was to be expected, as both the 2014 elections and the 2016 referendum were marked by a strong cleavage over the peace process, with Santos as the "pro-peace" candidate.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…21 The analysis also shows that other factors had an impact on support for the peace agreement. First, and in line with previous findings (Fergusson and Molina 2016;Liendo and Braithwaite 2018;Weintraub et al 2015), municipalities with higher levels of support for Santos in the 2014 presidential elections were more prone to vote yes in the referendum (p < 0.01). This was to be expected, as both the 2014 elections and the 2016 referendum were marked by a strong cleavage over the peace process, with Santos as the "pro-peace" candidate.…”
Section: Resultssupporting
confidence: 89%
“…For example, analyzing the 2014 presidential elections, Weintraub et al (2015) found that Juan Manuel Santos-the pro-peace candidate-performed well in communities with moderate levels of violence but poorly in communities with very high and low levels. Relying on 2014 AmericasBarometer survey data, which included a question about support for the then-ongoing peace process, Liendo and Braithwaite (2018) found that existing political preferences overwhelmingly drove attitudes toward the peace process with the FARC, not experiences of violence (see also Brodzinsky 2016).…”
Section: Exposure To Violence and Attitudes Toward Peacementioning
confidence: 99%
“…Lastly, it should not pass without comment that studies that analyze the results of the plebiscite in relation to geography show that the 'No' vote was predominant in medium-sized cities and in "the popular classes of major cities". Rural and border areas, which were the hardest hit by armed conflict, voted mostly in favor of the agreements (Basset 2018, p. 245;Liendo and Braithwaite 2018;Jiménez 2016). Though this fact cannot fully account for the phenomenon these authors have identified, it should be noted that it is precisely the 'popular classes' in large cities where the Pentecostal megachurches who led the opposition to the agreements have flourished.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite these results, recent research on the Colombian case showed that attitudes towards the peace process are not strongly correlated with conflict experiences (Hazlett and Parente, 2020;Liendo and Braithwaite, 2018), and that there are no differences in attitudes towards transitional justice mechanisms between victims and non-victims (Nussio et al, 2015). These counterintuitive findings may indicate that in a long-term civil conflict, the victims versus non-victims divide may be blurred.…”
Section: How War and Political Experiences Shape Citizens' Attitudes mentioning
confidence: 92%